Silkworm excrement organic fertilizer substitution compound fertilizer improves bamboo shoot yield by altering soil properties and bacterial communities of Moso bamboo (Phyllostachys edulis) forests in subtropical China - Yang, Zhenya; Zhao, Jiancheng; Ni, Huijing (Frontiers in Plant Science, 2025)
To achieve high economic benefits, reapplying fertilizers has been a common business measure taken for harvesting Moso bamboo shoots and timber in the past decades in subtropical China. Applying compound and organic fertilizers is an effective measure to enhance soil fertility and promote plant production. To demonstrate how compound fertilizer (CF) decrement and application of silkworm excrement organic fertilizer (SEOF) effect on soil quality, bamboo shoot yield and quality of Moso bamboo plantations, six CF decrement treatments (0 %, 25 %, 50 %, 75 %, and 100 % SEOF substitution, and no fertilization) were examined in our study. Soil nutrients, enzyme activities, bacterial community structures, bamboo shoot yield and quality were determined, and their relationships were analyzed. The results showed that adding SEOF improved soil quality and bamboo shoot yield. Compared with CF, the combined CF-SEOF treatments increased soil pH, soil organic carbon, N and P availability, and the activities of enzymes related to C, N, and P cycling. SEOF substitution significantly changed the soil bacterial community structure and increased the relative abundance of Proteobacteria and Actinobacteria. Higher proportions of organic fertilizer substitution (OF75, OF) enhanced the bamboo shoot yield (by 20.23 % and 16.55 %, respectively) and their total flavonoid and vitamin C content, compared to CF (p< 0.05). Moreover, the soil quality index of OF75 and OF50 was significantly higher than that of OF and OF25 in the 0–40 cm soil layer (p< 0.05). Pearson’s correlation tests showed that bamboo shoot yield was positively related with soil nutrients (p< 0.05). In addition, SEM revealed that fertilization affected soil enzyme activities through soil microorganisms, thereby affecting soil nutrient availability and promoting SQI and bamboo shoot yield. In conclusion, our study revealed that SEOF production is advisable for improving soil quality and bamboo shoot yield, providing evidence that soil nutrients and bacteria contribute to shoot yield and promote the sustainable management of soil and Moso bamboo forests.